Long-term speech perception and morphosyntactic outcomes in adolescents and young adults implanted in childhood. (April 2023) - Mancini, Patrizia; Nicastri, Maria; Giallini, Ilaria; Odabaşi, Yilmaz; Greco, Antonio; Dincer D'Alessandro, Hilal; Portanova, Ginevra; Mariani, Laura
Abstract: Background: Long-term assessments of children with cochlear implants (CI) are important inputs to help guide families and professionals in therapeutic and counselling processes. Based on these premises, the primary aim of the present study was to assess the long-term speech and language outcomes in a sample of prelingually deaf or hard of hearing (DHH) adolescents and young adults with unilateral or bilateral implantation in childhood. The secondary aim was to investigate the correlations of age at implantation with long-term speech and language outcomes. Materials and methods: Retrospective observational study on 54 long-term CI users, 33 unilateral and 21 bilateral (mean age at CI surgery 38.1 ± 24.6 months; mean age at last follow-up assessment 19.1 ± 4.3 years of age and mean follow-up time 16 ± 3.7 years). Means and standards were used to describe speech perception (in quiet, in fixed noise and in adaptive noise using It-Matrix) and morphosyntactic comprehension (TROG-2) outcomes. A univariate analysis was used to evaluate outcome differences between unilateral and bilateral patients. Bivariate analysis was performed to investigate the relationships between age at CI, audiological variables, and language outcomes. Finally, multivariate analysis was performed to quantify the relationship between It-Matrix, sentence recognition in quiet and at SNR+10 and TROG-2. Results: The participants showed good speech recognition performance in quiet (94% for words and 89% for sentences) whilst their speech-in-noise scores decreased significantly. For the It-Matrix, only 9.2% of the participants showed scores within the normative range. This value was 60% for TROG-2 performance. For both auditory and language skills, group differences for unilateral versus bilateral CI users were not statistically significant (p > 0.05). Bivariate analysis showed that age at CI correlated significantly with overall results at TROG-2 (r = −0.6; p < 0.001) and with It-Matrix (r = 0.5; p < 0.001). TROG-2 was negatively correlated with results for It-Matrix (r = −0.5; p < 0.001). In the multivariate analysis with It-Matrix as a dependent variable, the model explained 63% of the variance, of which 60% was related to sentence recognition and 3% to morphosyntax. Conclusions: These data contribute to the definition of average long-term outcomes expected in subjects implanted during childhood whilst increasing our knowledge of the effects of variables such as age at CI and morphosyntactic comprehension on speech perception. Although the majority of this prelingually DHH cohort did not achieve scores within a normative range, remarkably better It-Matrix scores were observed when compared to those from postlingually deafened adult CI users.